Diagnóstico del acceso de la ciudadanía a los servicios públicos según los programas de gobierno abierto y cercano, en el portal web del gobierno autónomo descentralizado municipal de Catamayo, año 2018 - Mendoza Torres, Danya Yazmin (2019)
The purpose of the present investigation is to carry out a DIAGNOSIS OF THE ACCESS OF THE CITIZENSHIP TO THE PUBLIC SERVICES ACCORDING TO THE OPEN AND NEARBY GOVERNMENT PROGRAMS, AT THE DECENTRALIZED AUTONOMOUS GOVERNMENT WEB PORTAL, YEAR 2018. The objective of the research is to describe the current situation of the Catamayo GAD web portal in consideration of public information and online services, as well as to determine the level of knowledge and use that citizens have regarding the web portal and establish strategies that help improve citizens' access to the public services of the portal. For the fulfillment of the objectives that support the investigation, tools were applied such as the observation to the web portal of the Municipal GAD of Catamayo, in addition, surveys were applied to 364 citizens of the urban parishes of Catamayo between the ages of 18 and 65 and it was carried out analysis matrices to establish strategies knowledge and use that citizens have regarding the web portal and establish strategies that help improve citizens' access to the portal's public services. The research was descriptive, since the current situation of the GAD web portal was described, as regards the research approach, the qualitative and quantitative one was applied, the first to give qualities to what was observed in the web portal and the second to examine the statistical data of the surveys applied. And the methods used were the scientist with which the research was theoretically based, also the analytical method since analyzes of the applied surveys and the matrices carried out were 6 carried out, and finally the deductive method that allowed obtaining information in a general way to then arrive to the specificity of the research problem. With the methodology and tools applied, the description of the web portal was carried out, resulting in the portal being obsolete and in an emerging e-government stage since it does not present updated information or accessible online services. Subsequently, surveys were applied which determined that the citizens of the urban parishes of Catamayo have a low level of knowledge and use of the portal, 11% of women and 14% of men do know about the web portal, compared to 41% of women and 34% of men who do not know about the existence of the web portal. It was also possible to determine the level of knowledge by age, obtaining that 17% of the population in young age and 7% of the adult population, do know about the portal, while 43% of the population in young age and 33 % of the population in adulthood do not know about the subject. The use is reflected with 34% of the population that can use the portal, while 66% cannot, therefore it is also low. And finally, strategies were established through matrices such as the Strengths, Opportunities, Weaknesses and Threats Matrix (SWOT), the Analytical Strategy Formation Matrix (MAFE), and the Quantitative Strategic Planning Matrix (MCPE), of which When giving an assessment, the strategy “Create the municipal electronic window” with a rating of 4.87, higher than the average total rating, and the strategy, “Use existing strengths in the web portal, to improve the provision of public services on the web portal, thus increasing citizen participation and cultivating digital culture in citizens ”with a rating of 2.93, lower than the average total rating. After that, the discussion and the appropriate conclusions and recommendations were carried out.